The Determinant Factors Of Work Productivity At Port Operating Company: Work Conflict, Work Stress And Leadership - Nur Widyawati; Nugroho Dwi Priyohadi; Siti Mutmainah; Joko Suyono (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: The purpose of this study was to determine the effect of work conflict, work stress and leadership on work productivity at the port operating company. Design / methodology / approach: The method in this study uses a quantitative approach with multiple linear regression analysis Findings: The study was conducted at the port operating company in Surabaya Research limitations / implications: Limits in the study use three independent variables and one dependent variable. The independent variables are work conflict, job stress and leadership. The dependent variable is the work productivity variable Practical Implications: The population is 164 employees and the study sample is 62 employees determined by the Slovin formula and random sampling. Originality / Value: This research was conducted at the port operating company Surabaya Paper type: Research paper